An Investigation of Novice Pre-University Students' Views towards MOOCs: The Case of Malaysia. Issue 2 (3rd April 2019) - Amantha Kumar, Jeya; Al-Samarraie, Hosam
ABSTRACT: There has been a growing number of studies dedicated to understanding how Massive Open Online Courses (MOOCs) impact the e-learning community. Yet, little is still known about how novice pre-university students perceive the use of MOOCs in Malaysia. This study explored pre-university students' perceptions of, challenges with, and intention towards MOOCs by using interview data. The results showed that students' general perceptions of the MOOC were positive, reporting that they gained additional knowledge, marks towards their Diploma and benefiting from the opportunity to create an online learning community. However, they were challenged by their language competency and awareness of MOOCs. Outcomes from this study may offer some practical implications to educational decision-makers in Malaysia towards promoting the use of MOOCs among students. Abbreviations : MOOC: Massive Open Online Courses; cMOOC: Connectivist Massive Open Online Courses; xMOOC: eXtended Massive Open Online Courses; ahMOOC: adaptive hybrid Massive Open Online Courses; LMS: Learning Management System; MQA: Malaysian Qualifications Agency; STEM: Science, Technology, Engineering, and Mathematics